2006
DOI: 10.1097/01.prs.0000187150.09737.1a
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Significant Sternocleidomastoid Atrophy following Modified Radical Neck Dissection Type III

Abstract: Despite evidence of significant atrophy, the muscle still underwent morphological changes during contraction that were comparable to those on the normal control side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…16 Preservation of the spinal accessory nerve and if preserved along with sternocleidomastoid muscle, result in better shoulder function, protection of neck arteries and cosmesis. 17,18 Therefore surgeons try to preserve accessory nerve etc., when oncologially feasible. Postoperative radiation therapy is recommended for cases with large nodal metastasis and extranodal spread.…”
Section: Discussionmentioning
confidence: 99%
“…16 Preservation of the spinal accessory nerve and if preserved along with sternocleidomastoid muscle, result in better shoulder function, protection of neck arteries and cosmesis. 17,18 Therefore surgeons try to preserve accessory nerve etc., when oncologially feasible. Postoperative radiation therapy is recommended for cases with large nodal metastasis and extranodal spread.…”
Section: Discussionmentioning
confidence: 99%
“… 6 – 8 These studies demonstrated significant SCM atrophy after mRND or selective neck dissection. Cuccia et al 7 reported the frequency and the extent of SCM atrophy after mRND type III using ultrasonography. They used the absolute asymmetry index (AAI).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage against the mean of bilateral SCM areas was considered to be more easily grasped than that against the sum, so AI was chosen for this study. Cuccia et al 7 declared that >10% on the AAI (same as 20% on the AI) represented severe asymmetry and found that it was observed in 98% of the caudal portion of the SCM and in 80% of the middle portion after mRND that spared the SAN. Ohtawa et al 6 similarly found atrophy in 90% of the caudal portion of the SCM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations